Two phase flow regime identification using infrared sensor and volume of fluids method. (October 2016) - Arunkumar, S.; Adhavan, J.; Venkatesan, M.; Das, S.K.; Balakrishnan, A.R.
Abstract: The simultaneous flow of two different phases is referred to as two phase flow. In the present study, a technique is developed for the identification of Air-Water two phase flow regimes using Infrared sensor. Experiments were done in a 4.7 mm borosilicate glass tube with a wall thickness of 0.3 mm. An Infrared (IR) emitter is used to send IR rays continuously. This IR ray is refracted by passing through the glass tube and the flowing medium. The refraction results in variation in current flowing through the IR receiver which is recorded online using data acquisition system. Bubbly, Slug and Stratified flow regimes were identified from the variation in current. Computational Fluid Dynamics (CFD) modeling of two phase flow inside the tube of same dimension was done using Volume of Fluids (VOF) method. Numerical simulations were carried out in Fluent 2D for the same superficial liquid and gas velocities as in the experiments. The results of the IR sensor and the Volume of Fluids method were compared with high speed photography of the two phase flow patterns. The flow patterns identified using IR sensor are in good agreement with the results of VOF method and high speed videography. Highlights: Two phase flows. Infrared sensor. Volume of fluids method. Bubbly, dispersed bubbly and stratified flow.